New insights on the Impacts of Public Agricultural Research and Extension on Agricultural Productivity: Evidence from the United States - Huffman, Wallace (Cuyonomics. Investigaciones en Economía Regional, 2017)
There is broad agreement on the importance of investments in productivityenhancing agricultural research and extension. Although estimated returns for the US are generally large, recent calculations differ greatly. The objective of this paper is to provide an economic assessment of the recent estimates and a guide to future public investments in this field.